The Implementation of Legal Protection Against Economic Exploitation of Street Children in Yogyakarta City - Fauzy, Rendi Rizaldi; Isnawan, Fuadi (Ius Poenale, 2024)
This research investigated the initiatives undertaken by the Yogyakarta City government to legally protect street children from economic exploitation. It focused on the roles of key institutions such as the Department of Social Affairs, Labors, and Transmigration in the city of Yogyakarta along with the local Children Protection Commissioner. The research explored the challenges these bodies faced in executing their duties. Utilizing empirical methods, interviews were conducted with relevant stakeholders including the head of the rehabilitation section of the Department of Social Affairs, the chairperson of the Indonesian Children Protection Commissioner in the district of Yogyakarta, and their team members. The findings revealed that despite numerous programs and regulations implemented by the Yogyakarta city government to protect the rights of street children, economic exploitation persisted primarily due to poverty. This research highlighted the gap between policy implementation and its effectiveness, suggesting a need for a review of existing measures and potentially the development of new strategies to address the economic exploitation of street children in Yogyakarta.